The effects of grade retention on human capital accumulation - Alex Solis (Uppsala University, Department of Economics, 2017)
Grade retention is a widely used educational policy promoting human capital. However,its benets and costs are still under debate. Retention may aect learning, cognitive and psychologicalcapacities, educational attainment and the lifetime income (through the timingof entry to the labor market). This paper estimates the causal eects of grade retention onall these outcomes exploiting a retention rule based on the school GPA that enables a regressiondiscontinuity design. I use administrative data from a 15-years panel on the universeof students in the educational system in Chile. The ndings are fourfold. First, (marginally)retained students achieve the same amount of education than (marginally) promoted(i.e., high school graduation, higher education enrollment, etc.). Second, they improve theircognitive ability (measured by test scores) in the short and the long run. Third, inducesparents to increase parental time investments and expectations. Fourth, enhances studentpsychological traits, and overall learning experience.
urn:nbn:se:uu:diva-337403
Keywords: I21; I26; I3; J24; 330; Grade retention; attainment; cognitive achievement; high school graduation; parental investmet; self-esteem; learning